Gas chromatography with mass spectrometry analysis of phosphoserine, phosphoethanolamine, phosphoglycerol, and phosphate - Bierhanzl, Václav Matěj; Čabala, Radomír; Ston, Martin; Kubinec, Róbert; Szabó, Alexandra Hengerics; Podolec, Peter (Journal of separation science, 2015)
A new, rapid, sensitive, robust, and reliable method has been developed for the qualitative analysis of phosphoserine, phosphoethanolamine, phosphoglycerol, and phosphate using gas chromatography with mass spectrometry and two-step trimethylsilylation. The method employs hexamethyldisilazane for silylation of the phosphate and hydroxyl groups in the first phase and bis(trimethylsilyl)trifluoroacetamide for silylation of the less-reactive amino groups in the second phase. This order is of key importance for the method because of the different reactivities of the two reagents and the mechanism of derivatization of the active groups of the analytes. Trimethylsilylated derivatives of the analytes were identified on the basis of their retention times and mass spectra. The probable structures of the major fragments were identified in the spectra of the trimethylsilylated derivatives and characteristic m/z fragments were selected for each analyte. Fragments with m/z 73 and 299 occurred in the spectra of all the analytes. The characteristic retention data were employed to calculate the retention indices of the individual silylated phosphorylated substances in the hydrocarbon range C12-C19 for the DB-5ms column. The method was employed to measure the polar fraction of the hydrolysate of the cytoplasmic membrane of Bacillus subtilis. The detection limits vary between 5 μg/mL (trimethylsilylated phosphate) and 72 μg/mL (trimethylsilylated phosphoethanolamine).
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Ethanolamines; Bacillus subtilis; Phosphates; Chromatography, Gas; fosfoserin; buněčná membrána; ethanolaminy; fosfáty; Phosphoserine; chromatografie plynová; Cell Membrane